USE OF FINANCIAL TECHNOLOGY AND THE ROLE OF FINANCIAL INCLUSION: A LITERATURE REVIEW - Baroto, Yatmoko; Prihatni, Rida; Gurendrawati, Etty (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to explore the relationship between financial technology (fintech), financial literacy, and financial inclusion, as well as their impact on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research employs a Systematic Literature Review (SLR) following PRISMA guidelines. Data were sourced from the Scopus database between 2018 and 2024, focusing on Q1 and Q2 journals. The search, using the keywords "Financial Technology" and "Financial Inclusion," initially identified 72 records, which were filtered down to 22 articles for the final review. The analysis reveals a significant upward trend in publications related to fintech and financial inclusion, particularly since 2019. The study highlights the importance of financial literacy as a prerequisite for effective financial inclusion, as well as the role of fintech in enhancing access to financial services for MSMEs. These findings provide insights for stakeholders and policymakers to prioritize financial education initiatives that empower MSME owners to effectively utilize fintech solutions, thereby improving their business performance.